A NEW LOOK AT THE AKKADIAN ROYAL RITUAL FOR AVERTING DIVINE ANGER. (December 2022) - Ni, Chunrong
Abstract : The Babylonian royal ritual text edited in this article prescribes the performance of two kinds of prayers: Šigû prayers and Emesal prayers. The text has four cycles, in each of which the target is one of the great gods (Marduk, Anu, Enlil, and Ea), as well as the minor gods functioning as intercessors on behalf of the king. The Marduk cycle is distinctive, compared with the other cycles, probably because of the special relation of Marduk with the king, kingship, and Babylon.